2013
DOI: 10.1007/s40265-013-0140-1
|View full text |Cite
|
Sign up to set email alerts
|

Prucalopride: A Review of Its Use in the Management of Chronic Constipation

Abstract: The highly selective serotonin 5-HT4 receptor agonist prucalopride (Resolor(®), Resotran(®), Resotrans(®)) is indicated for the treatment of chronic constipation. In four randomized, double-blind, multicentre, 12-week trials in patients (predominantly women) with chronic constipation, oral prucalopride 2 mg once daily improved bowel function to a significantly greater extent than placebo, with a significantly greater proportion of prucalopride than placebo recipients achieving an average of ≥3 spontaneous, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, there are several systematic reviews and meta-analyses evaluating the role of prucalopride [59][60][61][62][63][64][65][66][67][68] in the management of chronic constipation and their findings are consistent with the findings of the current study. Although the scope of the current article is the evaluation of clinical effectiveness and adverse events related to prucalopride only, previously reported systematic reviews [59][60][61][62][63][64][65][66][67][68] have reported its safety, efficacy, pharmacokinetics, and tolerability providing supporting evidence to our conclusions. As reported by Tack et al 69 "Prucalopride is an important addition to the therapeutic abilities for treating chronic constipation, especially in females poorly responding to laxatives.…”
Section: Discussionsupporting
confidence: 89%
“…[59][60][61][62][63][64][65][66][67] However, this study provides up to date, comprehensive and cumulative evidence on the use of prucalopride that meaningfully reduce symptoms related to chronic constipation. One review 59 reported the combined analysis of 3 trials, 4 reviews 62,64,65,67 reported the combined analysis of 4 trials each, 2 reviews 64,66 reported systematic review of the trials evaluating four 5-HT 4 agonist agents, whereas 3 reviews 60,61,68 were evidence reviews.…”
Section: Discussionmentioning
confidence: 98%
“…These cardiovascular side effects should thus not occur with the new generation of highly selective 5‐HT 4 receptor agonists such as prucalopride. Prucalopride was indeed found to be cardiovascularly safe in several randomized placebo‐controlled double‐blind trials in patients with chronic constipation; nevertheless combination therapies are explored to lower the dose and risk of adverse events. Combination of a 5‐HT 4 receptor agonist with the acetylcholinesterase inhibitor neostigmine had a synergistic effect on cholinergic activity in vitro in human colon and on colonic transit time in vivo in rat; the synergistic effect on cholinergic activity in vitro in human colon was confirmed with the acetylcholinesterase inhibitor donepezil .…”
Section: Discussionmentioning
confidence: 99%
“…Prucalopride, a highly selective and tissue‐specific 5‐HT 4 receptor agonist, has a well‐established efficacy and safety profile and is approved in Europe and Canada for CIC. Three randomized, double‐blind, placebo‐controlled 12‐week phase III trials were conducted in a total of 1974 patients with CIC who received prucalopride 2 mg, prucalopride 4 mg, or placebo once/day . The primary end point of occurrence of at least three CSBMs/week was achieved in 19.5–30.9% of patients receiving prucalopride 2 mg and 23.5–28.4% receiving prucalopride 4 mg, compared with 9.6–12.1% of patients receiving placebo (p < 0.01 for all comparisons vs placebo).…”
Section: Emerging Therapies For the Treatment Of Ibs‐cmentioning
confidence: 99%